Social and cultural conditions in light of the book “History of Bukhara” by Al-Narshakhi (d. 348 AH) (Journal of the College of Education for Women, 2025)
This research includes a study of the social and cultural conditions in Bukhara, based on an authentic source: the book "History of Bukhara" by al-Narshakhi. This book is considered an important historical book, containing valuable information about one of the most important cities in the Islamic East, Bukhara, during the era of al-Narshakhi's reign. This era was marked by the Samanid dynasty, and the rulers' interest in social, cultural, and economic aspects. Bukhara was one of the most important scientific and cultural centers, rivaling Baghdad, the capital of the Abbasid Caliphate, as many scholars and thinkers visited it. The princes were keen to encourage and disseminate knowledge, as well as translation and authorship. The geographical location played a significant role in the diversity of social classes and groups. I used a descriptive and analytical approach to analyze the content of the book, analyzing the scientific material, and supplementing and complementing it through other sources and studies, which contained scientific material.